2017
DOI: 10.1002/oby.22007
|View full text |Cite
|
Sign up to set email alerts
|

Change in Physical Activity During a Weight Management Intervention for Breast Cancer Survivors: Association with Weight Outcomes

Abstract: Objective The study examined the effects of a group-phone based weight management intervention on change in physical activity as measured via accelerometer and self-report in rural breast cancer survivors. The study also evaluated the role of physical activity on clinically meaningful cut-points for weight loss (baseline to 6 months) and weight loss maintenance (6 to 18 months). Methods Participants were breast cancer survivors in a weight management intervention who provided valid weight and accelerometer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 34 publications
(51 reference statements)
3
43
0
Order By: Relevance
“…These results support this finding that perhaps an emphasis on weight maintenance during and after treatment is a key component of survivorship care-planning. Rather than emphasis on weight loss, perhaps the approach and future research should surround weight maintenance (or prevention of weight gain) that involves increased physical activity and dietary adjustments, both known to reduce fatigue, increase cardiovascular health, and perhaps decrease body fat percentages[27]. Our findings support the notion that survivorship care-planning should involve the patient and should factor in age, commuting region, late side-effects, and health promotion[2,28].…”
Section: Discussionmentioning
confidence: 99%
“…These results support this finding that perhaps an emphasis on weight maintenance during and after treatment is a key component of survivorship care-planning. Rather than emphasis on weight loss, perhaps the approach and future research should surround weight maintenance (or prevention of weight gain) that involves increased physical activity and dietary adjustments, both known to reduce fatigue, increase cardiovascular health, and perhaps decrease body fat percentages[27]. Our findings support the notion that survivorship care-planning should involve the patient and should factor in age, commuting region, late side-effects, and health promotion[2,28].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term health benefits should continue to be investigated, as many current studies only assessed an intervention period of 12 weeks. However, recent literature has suggested HWT to yield behavioral impacts in some populations for upwards of 18 months post-intervention [ 13 , 35 ]. Employment of long-term follow-up observations should be strongly considered for future studies in this field of inquiry [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, another study comparing various cancer survivor groups found that BCS, specifically, tended to have the greatest ability to improve physical activity behaviors during a technology-based intervention [ 8 ]. Not only are technology-centered interventions effective during experimental trials but a longitudinal follow-up study also observed improvements in HRQoL factors among BCS at 18 months post-intervention [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not only can a health professional gain accurate data regarding the patient's progress, it removes the need for a patient to recall past events, removing overestimates, underestimates, and "doctor-pleasing" answers from the equation which patients may give if they have not adhered closely to the program, such as the case with the study performed by Fazzino, Fabian, and Befort (Fazzino, Fabian, and Befort, 2017). This allows for the regimen to be performed on a more quantitative basis, such as with a pedometer, accelerometer, or calorie counter.…”
Section: Palliative Carementioning
confidence: 99%